Numerical Study on Zonal Disintegration of Deep Rock Mass Using Three-Dimensional Bonded Block Model - Qingteng Tang; Wenbing Xie; Xingkai Wang; Zhili Su; Jinhai Xu (Advances in Civil Engineering)
Zonal disintegration, a phenomenon of fractured zones and intact zones distributed alternately in deep rock mass, is different from the excavation-damaged zone of shallow rock mass. In this study, bonded block model of 3DEC was employed to study the fracture mode and origination condition of zonal disintegration. Initiation, propagation, and coalescence progress of fracture around the roadway boundary under different triaxial stress conditions are elaborated. Numerical simulation demonstrated that zonal disintegration may occur when the direction of maximum principal stress is parallel to the roadway axis. It is interesting to find that the fracture around the roadway boundary traced the line of a spiral line, while slip-line fractures distributed apart from the roadway boundary. The extent of the alternate fracture zone decreased as the confining pressure increased, and alternate fracture zone was no longer in existence when the confining pressure reaches a certain value. Effects of roadway shape on zonal disintegration were also studied, and the results indicated that the curvature of the fracture track line tends to be equal to the roadway boundary in shallow surrounding rock of the roadway, while the fractures in deep surrounding rock seems unaffected by the roadway shape. Those findings are of great significance to support design of deep underground openings.